Reconstructing Curriculum Management As A Key Pillar of Realising Educational Equity in Marginalised Schools - Khalidi, Ahmad (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study investigates the reconstruction of curriculum management in marginalised schools through the lens of educational justice. Using a critical narrative approach, the research examines the challenges faced by schools in Amuntai, South Kalimantan, where the top-down national curriculum model fails to meet local needs and contexts. The study explores how national policies, despite their intentions to standardise education, exacerbate educational inequalities in rural settings. Data were collected from teachers, school principals, and students through in-depth interviews, participatory observations, and document analysis. The study employs Critical Narrative Analysis (CNA) for data analysis, involving three stages: organising the data into thematic categories, interpreting these themes to identify recurring patterns, and deconstructing the ideological narratives underlying curriculum practices. The findings indicate that while teachers demonstrate local initiative in adapting the curriculum to better suit their students’ needs, their efforts are largely unrecognised by formal educational authorities, and their involvement in curriculum decision-making is minimal. This lack of recognition limits the sustainability of local adaptations. The study argues that a more flexible, participatory curriculum design is required—one that values local knowledge and practices and empowers teachers and students to contribute to decision-making. It highlights that curriculum reform, rooted in the principles of educational justice, should focus on equitable representation, recognition, and redistribution of educational resources. Ultimately, this research provides recommendations for creating an inclusive educational system that acknowledges the specific needs of marginalised communities and supports local contexts in shaping curriculum design.